KETERAMPILAN MENYIMAK SISWA SEBAGAI BENTUK KEMAHIRAN BERBAHASA INDONESIA DI SMK DARUL IJTIHAD PARAJIN BANYUMAS SAMPANG - Asri Bariqoh; Ajeng Ananda Putri Lestari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2023)
Listening skills are important for students which must be developed to sharpen memory and responsiveness in learning in the classroom and to train a student's focus. This research is a qualitative research. While the method used in data collection is the method of interviews, observation and documentation. The data analysis used is data reduction to choose focus, simplicity, abstracting and transforming data that emerges from field notes, then proceed with presenting data, then the data will be organized, arranged in a relationship pattern, so that it is easier to understand and then Verification or conclusion. The results of the research according to the focus of the research found: (1) from the video given by the researcher to class X students of SMK Darul Ijtihad Parajin Banyumas Sampang, only 60% were said to be proficient or 15 students could be said to be superior with a score of 578-640 and 40% could be said to be intermediate with score 482-577 (2) Factors supporting students' listening skills as a form of Indonesian language proficiency in class X at SMK Darul Ijtihad Parajin Banyumas Sampang are physical, psychological, motivational, gender, and community roles. (3) The inhibiting factor for students' listening skills as a form of Indonesian language proficiency is the students themselves who play an important role in listening skills in learning Indonesian.